Between artists and not atistis, a sociological anslysis of production and the misical biography of Raul Seixas - Souza, Lucas Marcelo Tomaz de (2012)
Between the two extremes represented by the artists and their production, a number of historical subjects engage theirselves in the aesthetics of the artist’s creations. In this work, we came to do an analysis of the biography of Raul Seixas, supported by a methodology proposed by Pierre Bourdieu, which places the creative artist in the foreground, in order to understand how the social legacy of the singer, arising from family relationships, might outline specifics aspects on his music production. In the same perspective, we intent to reflect how historical subjects, such as music producers, marketers, labels as well as radio, television and other means of communication, could direct the musical production of the singer from the consolidation of a market for symbolic goods in Brazil. Thus, we will think about the structuring of the field of Brazilian music during the seventies, and especially the singer’s position and rock inside of it, detecting how the forms of cultural production, that became legitime during the period, could prioritize forms of musicals productions able to delegate to other forms of art, strange to them, a space of inferiority within that field. To this end, we used a series of testimonials from singer, transcribed in books, magazines and newspapers, and a series of articles that address topics related directly or indirectly.